Essays on Classical and Marxian Political Economy : Collected Essays IV. - Hollander, Samuel (Routledge studies in the history of economics., 2013)
Samuel Hollander's work has been provoking debate for over four decades. This book brings together key contributions of recent years, in addition to some brand new pieces. The essays are introduced by a Preface in which Hollander reflects on his past work and reactions to it. Highlights include two issues of particular current relevance. Conspicuous is an extensive chapter regarding Adam Smith's often neglected arguments for government intervention in the economy to correct market failures, and his critical view of the business class as an anti-social force. Important economists consi.